Tingkat Kepercayaan Publik Terhadap Media Daring Lokal Terverifikasi Dewan Pers di Kalimantan Timur - Yusuf, Ibrahim; Muh Akbar; Alem Febri Sonni (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2024)
The amount of widespread information from various kinds of media makes public trust in the media decrease. This trust can be increased through local online media compared to national-scale media. This study aims to determine the level of public trust in news published by local online media verified by the Press Council. The design of this study is a quantitative approach with a sample of 400 East Kalimantan communities grouped by regency/city with random sampling division and can represent the number of each region. Quantitative descriptive statistics and linear regression analysis were used to see a picture of the level of public trust and see the relationship between the level of public trust in local online media verified by the press council. The results showed that the level of trust of the people of East Kalimantan regarding local online media verified by the press council was 77%, with the category of trust. Then for the influence of local online media verified by the press council on the level of public trust in East Kalimantan, significant results were obtained, meaning that local online media verified by the press council had an influence on the level of public trust in East Kalimantan.